Asimetrías de poder en relación a la violencia de género en la región sur del Ecuador. - Soria Villafuerte, Tamara Michell (2025)
This study addresses the persistent issue of gender-based violence, rooted in deeply entrenched sociocultural structures, where women encounter economic, legal, and social barriers that hinder their ability to escape abusive situations. The overarching objective was to interpret the asymmetries associated with gender-based violence in southern Ecuador from a public health perspective. An analytical and descriptive methodology was employed, including a documentary analysis of 27 academic articles published between 2018 and 2024. These articles were selected based on eligibility criteria from scientific databases. Percentages were analyzed using statistical tools, specifically IBM SPSS, to identify patterns of aggression. The findings reveal that structural violence is the most prevalent form, marked by limited access to resources and opportunities, perpetuated by norms that uphold the subordination of women. High levels of physical and psychological violence were also identified, particularly within family settings. The study concludes that multiple power imbalances contribute to the persistence of gender- based violence, highlighting the urgent need for multisectoral intervention strategies.